Influence Of Micro Local Organism And Media Of Fertilizer On Growth And Result Of Plant Of Selada (Lactuca Sativa L.) - Abdul Wachid; Emilda Agustina (Nabatia, 2018)
The aim of this research is to know the influence of local micro organisms and cropping media on the growth and yield of lettuce crops. The study was conducted in May-July 2017 using Group Random Design (RAK) with 2 factors repeated 3 times. The first factor consists of three levels of local micro organisms of kipahit leaf, water of laryers and fish innards. The second factor is planting media of cow manure, goats and chicken with 50% combination with soil. Observation with parameters of plant length, number of leaves, stem diameter, wet weight of trimming, wet weight of consumption and dry weight of berangkasan. Analysis of statistical data used is the analysis of variance as well as to determine the effect of treatment followed by the test of Beda Nyata Jujur (BNJ) at 5% level. The result of this research is the interaction of the influence of local micro organisms and cropping media on the growth and yield of Lettuce plants on leaf number of age 56 HST. Treatment of local micro organisms influenced growth and yield of Lettuce plants at age 28 HST with the highest value on treatment M3 (jeroan fish) that is 17.50 fruit. The treatment of cultivation media of manure occurred influence on growth and yield of lettuce crop at age 63 HST and who get highest value that is at K3 (chicken manure).